2016
DOI: 10.1111/bjh.13916
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and haematological risk factors for cerebral macrovasculopathy in a sickle cell disease newborn cohort: a prospective study

Abstract: Children with sickle cell disease (SCD) have a significant vascular morbidity, especially cerebral macrovasculopathy (CV), detectable by transcranial Doppler. This study aimed to identify risk factors for CV using longitudinal biological and clinical data in a SCD newborn cohort followed at the Robert Debre Reference centre (n = 375 SS/Sβ(0) ). Median follow-up was 6·8 years (2677 patient-years). Among the 59 children presenting with CV, seven had a stroke. Overall, the incidence of CV was 2·20/100 patient-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 69 publications
2
34
1
Order By: Relevance
“…However, this finding differs from previous published studies, associating low IL-10 levels with vaso-occlusive crises, 16 osteomyelitis, 31 and acute chest syndrome 29 in patients with SCA. Furthermore, this contradicts a previous study showing that a lower serum IL-10 level is associated with ischemic stroke in the general population 32 …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, this finding differs from previous published studies, associating low IL-10 levels with vaso-occlusive crises, 16 osteomyelitis, 31 and acute chest syndrome 29 in patients with SCA. Furthermore, this contradicts a previous study showing that a lower serum IL-10 level is associated with ischemic stroke in the general population 32 …”
Section: Discussioncontrasting
confidence: 99%
“…The overall frequency of IL10 haplotypes found in this study was similar to that reported in a recent study conducted in adult individuals with SCA from the northeastern region of Brazil 29 . The present study found slightly higher frequencies of haplotypes associated with high and intermediate IL10 expressions.…”
Section: Discussionsupporting
confidence: 91%
“…In a large cohort study, Belisario et al () reported that reticulocyte count was significantly associated with a high TCD velocity. Reticulocytes have been implicated in the aetiology of cerebral macrovasculopathy; they are markers of marrow activity and haemolysis, can cause endothelial activation and subsequent damage (Platt, ; Switzer et al , ; Kato et al , ; Sommet et al , ), and are thus likely contribute to abnormal cerebral rheology and vaso‐occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…There has been great interest in looking at the clinical, laboratory and genetic factors that are associated with abnormal TCD. There is good evidence to support a higher risk of abnormal TCD for patients with low haemoglobin, high reticulocyte count, high systolic blood pressure, and upper and lower respiratory tract obstruction whilst presence of alpha thalassaemia and high fetal haemoglobin levels (Sommet et al , ) have a protective effect. Beyond these generally accepted markers, the evidence is largely conflicting and unclear.…”
Section: Stroke In Sickle Cell Diseasementioning
confidence: 99%